Exploring Greece's Relationship with the Mediterranean Arab World: A Focus on the Cypriot and Palestinian Issues - Σουλτάνη, Ουρανία (Πανεπιστήμιο Πελοποννήσου, 2023)
The present study examines Greece's diplomatic, political, and economic relations with Cyprus and the Arab world, with a particular focus on the Cyprus and Palestinian issues. It begins with a historical overview of the developments in Cyprus, highlighting Turkey's invasion in 1974 and subsequent events. Emphasis is given on the actions of Prime Ministers Konstantinos Karamanlis, Andreas Papandreou, Konstantinos Mitsotakis, and Kostas Simitis, which were oriented towards resolving the issue within Western world and Eastern Mediterranean states. The study underscores Greece's consistent and unwavering support for successive Cypriot governments. Similarly, this work provides a historical retrospective on the genesis of the Palestinian issue and its relationship with Arab countries. It investigates Greece's stance on the Palestinian matter, highlighting the solidarity of the Greek state, especially during the tenure of Prime Minister Papandreou. Additionally, it discusses the efforts of all Greek governments to maintain balances with Eastern Mediterranean countries. Greece forges alliances with the Arab world and strengthens its position in the Western world to actively contribute to problem resolutions. Finally, the study concludes by examining Greece's current economic, energy, military, and diplomatic agreements with Cyprus, Israel, Egypt, and other Arab nations.
Keywords: Ελλάδα--Εξωτερικές σχέσεις--Αραβικές χώρες; Κύπρος--Εξωτερικές σχέσεις--Αραβικές χώρες; Greece’s diplomacy; Cyprus Conflict; Palestinian Conflict; Alliances with Arab world; Konstantinos Karamanlis; Andreas Papandreou; Konstantinos Mitsotakis; Kostas Simitis; Europeanization